A data-driven framework for effective single-group cross section adjustment in point-depletion burnup calculations - Wei-Jia Meng; Te Sheng; Ou-Yi Li; Gang-Lin Yu (Annals of Nuclear Energy, 2026)

Chitinase-primed ultrasound enhances Saccharomyces cerevisiae cell-wall deconstruction and yeast-protein remodelling in two complementary model systems - Talha Riaz; Xianjiang Ye; Te Yu; Zhijun Xia; Muhammad Moeid Khan; Xuan Yao; Rabiya Riaz; Sadia Ansar; Zhou Chen; Muhammad Atiq Ashraf; Chuanyan Pan; Yongguo Jin; et al. (Food Research International, 2026)

Halide defect driven nickel vanadate nanospheres applied as an electrochemical platform for the detection of gantrisin drug sulfisoxazole for human health monitoring - Sri Balaji Natarajan; Rajendran Surya; Tse-Wei Chen; Shen-Ming Chen; Te-Wei Chiu; Elayappan Tamilalagan; Chen-Chi Wang; Ming-Chin Yu; Heng-Yuan Hsu (Journal of Environmental Chemical Engineering, 2026)

Factors shaping nickel bioavailability and isotopic signatures in marine phytoplankton - Tzu-Hao Wang; Qiong Zhang; Yu-Te Hsieh; Gideon M. Henderson; Rosalind E.M. Rickaby (Geochimica et Cosmochimica Acta, 2026)

Real-world onboard evaluation of exhaust aftertreatment effects on particle-bound persistent free radicals and reactive oxygen species generation potential from inland vessels - Yu-Chieh Wang; Wei-Min Ching; Hsi-Hsien Yang; Yen-Hsien Li; Tzu-Hsien Tseng; Hsin-Te Yu (Environmental Pollution, 2026)

Corrigendum to “Mg-doped CoCr₂O₄ nanoparticles with fast humidity sensing and mixed-controlled pseudocapacitive charge storage” [Chem. Eng. J. 535 (2026) 175200] - K. Manjunatha; Shih-Lung Yu; Yi-En Wu; Ming-Kang Ho; Tsu-En Hsu; Yun-Tai Yu; B. Chethan; Mithun Prakash Ravikumar; Sakar Mohan; Tsung-Te Lin; Yi-Ru Hsu; Meng-Chu Chen; et al. (Chemical Engineering Journal, 2026)

Longitudinal association between dietary quality trajectories and cognitive frailty in older adults: a 12-year study of the TIGER cohort - Ting-I. Lee; Bo-Yu Hsiao; Te-Hsuan Huang; Ling-Wei Chen; Yi-Chun Chou; Meei-Shyuan Lee; Jeng-Min Chiou; Yen-Ching Chen; Jen-Hau Chen (GeroScience, 2026)

Simvastatin enhances the antitumor activity of temsirolimus through AMPK-associated metabolic modulation in clear-cell renal cell carcinoma - Hsuan-Yu Chen; Chien-Jui Cheng; Te-Hsing Hsu; Szu-Yu Tung; Fang-Ning Chou; Mantosh Kumar Satapathy; Shu-Hui Juan (Naunyn-Schmiedeberg's Archives of Pharmacology, 2026)

Enzymatic synthesis of a new and bioactive dihydrochalcone: 3,4-dihydroxy-2′,6′-dimethoxy dihydrochalcone - Te-Sheng Chang; Jiumn-Yih Wu; Hsiou-Yu Ding; Tzi-Yuan Wang; Guan-Cheng Liu; Min-Lin Wang; Huei-Ju Ting (Natural Product Research, 2026)

Synthesis and production of hydroxytyrosol derivatives with potent anti-inflammatory activities - Te-Sheng Chang; Wen-Yueh Ho; Jiumn-Yih Wu; Chien-Yu Wu; Pei-Rong Cai; Bo Eng Cheong; Wilson Thau Lym Yong; Peik Lin Teoh (Natural Product Research, 2026)

Enhanced dimethylsulfide emissions following eutrophication remediation in a coastal bay: biogeochemical and hydrological controls - Xiao-Ran Li; Jin-Wei Wu; Xiao-Song Zhong; Hao Qiao; Shi-Bo Yan; Feng Xu; Yu-Cheng Jiang; Rui-Te Zhang; Yu-Hao Qiu; Hong-Hai Zhang (Progress in Oceanography, 2026)

Lysozyme as a protein-based carrier for bioactives: advances in delivery systems and gut environment interactions - Te Yu; Yuzhong Zheng; Yongping Huang; Yuan Ma; Grażyna Neunert; Jie Cao; Xing Fu (Trends in Food Science & Technology, 2026)

First complete coding sequence of ovine herpesvirus 2 from a malignant catarrhal fever case of Formosan sambar deer in Taiwan: Genomic characterization and molecular epidemiology - Ruei-Sheng Tsai; Shih-Te Chuang; Hau-You Tzeng; Fong-Yuan Lin; Ching-Yu Tseng; Yi-Chen Chen; Wei-Li Hsu (The Veterinary Journal, 2026)

Capacitive sensor-based artificial stratum corneum for skin irritating assessment of botanical insect repellent products and a de-irritation formulation - Yun-Hsuan Cheng; Po-Chung Chen; Hung-Yu Chen; Chung-Ting Cheng; Yung-Te Hou; Tzong-Jih Cheng (Food and Chemical Toxicology, 2026)

Dang-Gui-Bu-Xue-Tang triggers GM-CSF and IL-4 secretion corporated with increased amount of Immunoglobulins - Sheng-Teng Huang; Jia-Hau Yen; Yu-Chun Lin; Ming-Ching Kao; Chia-Ju Chuang; Shu-Tuan Chiang; Te-Mao Li (Advances in Traditional Medicine, 2026)

Retrieval of cotton defoliation rate using random forest model based on rate of vegetation index change - Yukun Wang; Chenyu Xiao; Te Zhang; Xinghua Yu; Yao Wang; Yunxin Xu; Fangjun Li; Sumei Wan; Guodong Chen; Xiaoli Tian; Xin Du; Mingwei Du; et al. (European Journal of Agronomy, 2026)

Mg-doped CoCr2O4 nanoparticles with fast humidity sensing and mixed-controlled pseudocapacitive charge storage - K. Manjunatha; Shih-Lung Yu; Yi-En Wu; Ming-Kang Ho; Tsu-En Hsu; Yun-Tai Yu; B. Chethan; Mithun Prakash Ravikumar; Sakar Mohan; Tsung-Te Lin; Yi-Ru Hsu; Meng-Chu Chen; et al. (Chemical Engineering Journal, 2026)

Chitosan and γ-polyglutamic acid interfacial polyelectrolyte complexation fibers for tendon biomimicry and regeneration - Hao-Xuan Chen; Shih-Heng Chen; Shih-Hsien Chen; Yu-Chung Liu; Chen-Te Wu; Jian-Xun Chen; Tzu-Wei Wang (Carbohydrate Polymers, 2026)

Examining the utility of barium isotopes as a tracer of large-scale seafloor methane venting - Ethan Petrou; Luke Bridgestock; Germain Bayon; Nolwenn Lemaitre; Ya-Zhen Wu; Gideon M. Henderson; Yu-Te Hsieh (Marine Chemistry, 2026)

Impacts of period-specific particulate matter exposure on COPD phenotypes: Rapid lung function decline - Po-Hao Feng; I-Jung Liu; Rachel Chien; Kang-Yun Lee; Kuan-Yuan Chen; Wen-Te Liu; Ying-Ying Chen; Yen-Ling Chen; Kun-Ta Lee; Shu-Chuan Ho; Arnab Majumdar; Jiunn-Horng Kang; et al. (Atmospheric Environment, 2026)

Investigating temporal PM2.5 exposure in relation to rapid lung-function decline among COPD patients: A retrospective study - Kang-Yun Lee; Rachel Chien; Kuan-Yuan Chen; Ying-Ying Chen; Wen-Te Liu; Po-Hao Feng; Kun-Ta Lee; Shu-Chuan Ho; Arnab Majumdar; Jiunn-Horng Kang; Wun-Hao Cheng; I-Jung Liu; et al. (Atmospheric Pollution Research, 2026)

Trace metal and rare-earth element concentrations and distribution in freshwater-estuarine karst subterranean river benthic organisms, the Philippines - Frank Paolo Jay B. Albarico; Genese Divine B. Cayabo; Rodulf Anthony T. Balisco; Ming-Huang Wang; Mark Ariel D. Malto; Wen-Chien Huang; Te-Yu Liao; Chiu-Wen Chen; Cheng-Di Dong (Marine Pollution Bulletin, 2026)

Additive-mediated controlled growth of printed perovskite for planar and heterostructure solar cells - Anjali Thakran; Yen-Yu Wang; Rohan Paste; Atul Dhage; Yu-Te Chen; Mario Hofmann; Yu-Jung Lu; Chung Hsin Lu; Shih- I. Lu; Yan-Duo Lin; Chih Wei Chu (Chemical Engineering Journal, 2026)

Amine-promoted carbonation-electrodialysis for CO2 mineralization of waste gypsum: Toward a closed alkaline loop - Long Ji; Yan Wang; Yonggang Jin; Te Tu; Dazhi Yao; Shuiping Yan; Hai Yu (Chemical Engineering Journal, 2026)

Resistance of shallow soil carbon to both short-term isolated and recurrent droughts in two semi-arid grasslands - Taofeek O. Muraina; Niwu Te; Saheed O. Jimoh; Robert Griffin-Nolan; Lin Song; Jiaqi Chen; Yuan Shi; Ahmed A. Amisu; Tilak Chaudhary; Qiang Yu; Melinda D. Smith; Alan K. Knapp; et al. (Oecologia, 2026)

Lentipes ptasan , a new species of sicydiine goby (Teleostei: Gobioidei) from the Western Pacific, with a redescription of L. mindanaoensis - Wei‐Cheng Jhuang; Cleto L. Nañola; Xiao Fei Li; Te‐Yu Liao (Journal of Fish Biology, 2026)
Lentipes ptasan sp. nov. is described based on specimens collected from Taiwan and Mindanao Island. It is a large‐sized Lentipes species distinguished by several male‐specific characteristics, including an upper lip protruding beyond snout obviously, fewer premaxillary tricuspid teeth, two black lines running from the front of the eye through the nostrils to the tip of the snout, a wide brown longitudinal band at the base of the anal fin, and the distinctive nuptial coloration featuring a brown vertical band extending from back to belly on the middle of the body. The complex distribution of Lentipes species and their genetic differentiation may be influenced by sexual selection, historical biogeographic events and contemporary ecological processes. However, due to the recent divergence of Lentipes species, 11 out of 14 species could not be distinguished by the cytochrome oxidase subunit I gene. Furthermore, Lentipes mindanaoensis is redescribed, with L. adelphizonus treated as its junior synonym.

Environmental DNA metabarcoding enriches the conventional survey of a high diverse fish community in the Dongsha atoll - You-Chen Liu; Yi-Ching Yang; Kang-Ning Shen; Chun-Huo Chiu; Te-Yu Liao (Frontiers in Marine Science, 2026)
To effectively conserve coral reef ecosystems, it is essential to monitor changes in fish fauna using minimally invasive methods. In this study, we conducted a fish survey in the Dongsha Atoll using eDNA metabarcoding. Analyzing 37 sequencing units from 26 water samples collected across 12 sites from May 2017 to September 2018, we identified 421 species from 79 families. Among these, 192 species had not been recorded in previous conventional surveys. Some of these newly recorded species are fast-swimmers, while others may be larvae or eggs, which are challenging to observe visually. However, 68% of species documented in previous records were not detected in our study. This limitation is likely due to insufficient samplings, primer specificity, fish characteristics, and rapid DNA degradation in the dynamic physical and chemical conditions (e.g., temperature, pH) of the coastal environment. Despite that eDNA metabarcoding cannot capture the full range of species within the atoll, it effectively complements visual census surveys by enriching our understanding of the diverse fish community in marine habitats.

Collision avoidance for maritime autonomous surface ship in busy waterways based on the improved deep reinforcement learning and K-means clustering - Hui Yu; Defeng Wu; Guoqiang Li; Te Lian; Yuqin Li; Fusheng Li (Ocean Engineering, 2026)

Molecular-scale insights into the freeze-thaw process of aqueous and saline solutions in hydrated‑calcium-silicate gel pores - Jiachuan Ran; Yuanming Lai; Mingyi Zhang; Fan Yu; Te Liang; Wansheng Pei; Hongwei Li; Xulong Gao; Jiwei Jia (Cold Regions Science and Technology, 2026)

The impacts of hyperspectral infrared sounding assimilation for cloud-resolving model quantitative precipitation forecasts in Taiwan Mei-yu rainfall events - Chung-Chieh Wang; Yu-Te Sung; Chian-Yi Liu; Chih-Sheng Chang; Kazuhisa Tsuboki; Shen-Cha Hsu (Atmospheric Research, 2026)

Variation in the catch rate and distribution of three important commercial Spanish mackerel (Commerson: Niphonius: Guttatus) related to ENSO events around the waters off Taiwan - Lu-Chi Chen; Jinn-Shing Weng; Kuo-Wei Lan; Chen-Te Tseng; Cheng-Hsin Liao; Wei-Yu Lee; Irene Chia-Ling Lim (Regional Studies in Marine Science, 2025)

Sustainable energy generation through engineered copper molybdate: a ternary metal oxide catalyst for efficient oxygen evolution in alkaline environments - Hung-Chang Cheng; Dhanapal Vasu; Hsin-Yu Lin; Zhen-Yuan Lan; Leggins Abraham; Tetsu Yonezawa; Te-Wei Chiu (Fuel, 2025)

Ultrasound-assisted shear homogenization for preparing chitin nanocrystal-stabilized Pickering emulsions - Yimeng Lou; Te Yu; Binyan Zeng; Muhammad Moeid Khan; Nikolai Kuhnert; Ok-Hwan Lee; Xing Fu (Food Chemistry, 2025)

Feasibility analysis of using bacteriophage to treat acute hepatopancreatic necrosis disease in shrimp aquaculture - Hui-Yu Shih; Te-Ken Hsu; Li-Li Chen (Fish & Shellfish Immunology, 2025)

Integrated metabolomics reveals immunomodulatory compounds in giant African snail (Achatina fulica) extracts for the giant river prawn (Macrobrachium rosenbergii) - Youshang Lin; Chen-Hsun Liu; Chiu-Hui Kuo; Bonien Chen; Wei-Ming Wu; Tsung-Meng Wu; Te-Yu Liao; Kuohsun Chiu (Fish & Shellfish Immunology, 2025)

Development and validation of a five-channel multiplex LC−ESI−MS/MS method for the quantification of carboxylic acids in urine - Wan-Hui Lu; Ju-Yu Chen; Te-I Weng; Ching-Hua Kuo; Guan-Yuan Chen (Analytica Chimica Acta, 2025)

Evolving heat risk inequality in relation to changes in green infrastructure of cities in Northern Taiwan - Wan-Yu Shih; Te-Lun Ouyang (Sustainable Cities and Society, 2025)

Chitin nanofiber-stabilized pickering emulsions loaded with citrus essential oil: Characterization and application for pork preservation - Ge Wang; Te Yu; Jiran Lv; Linhua Huang; Ok-Hwan Lee; Xing Fu (Food Research International, 2025)

Correction to: Enhancing triterpenoids production in Ganoderma multipileum submerged cultures using caffeine as a P450 inducer and limonene as a precursor - Te-Wei Ma; Yu-Huan Chang (World Journal of Microbiology and Biotechnology, 2025)

Synergistic effects of nano-heterostructured layered materials for efficient hydrogen generation via water splitting and urea oxidation, and photocatalytic remediation of food coloring agent wastewater - Dhanapal Vasu; Yu-Tong Huang; Te-Wei Chiu; Sheng-Chi Chen; Shih-Hsien Chang (Journal of Environmental Management, 2025)

Experimental and numerical study on vibration attenuation performance of 3D printed single-phase metamaterial plate with broad low-frequency complete bandgap - Te-Han Chu; Sheng-Hsiang Tsai; Yu-Jui Liang (Engineering Structures, 2025)

Association between air pollution and obstructive sleep apnea in terms of respiratory event frequency and lung-to-finger circulation time - Rachel Chien; Zhihe Chen; Peizheng Wang; Wen-Te Liu; Ying-Ying Chen; Yen-Ling Chen; Arnab Majumdar; Jiunn-Horng Kang; Kang-Yun Lee; Wun-Hao Cheng; Yi-Chih Lin; Cheng-Jung Wu; et al. (Atmospheric Pollution Research, 2025)

Enhancing triterpenoids production in Ganoderma multipileum submerged cultures using caffeine as a P450 inducer and limonene as a precursor - Te-Wei Ma; Yu-Huan Chang (World Journal of Microbiology and Biotechnology, 2025)

Fine root trait dynamics and their relationships with productivity across grasslands under extreme drought - Yuan Shi; Taofeek O. Muraina; Saheed O. Jimoh; Niwu Te; Lin Song; Jiaqi Chen; Hongqiang Wang; Qiang Yu; Xiaoan Zuo; Xingguo Han; Wentao Luo; Scott L. Collins (Oecologia, 2025)

Mechanisms of groundwater recovery and land subsidence mitigation in a piedmont plain - Long Zhao; Xiao-Wei Jiang; Yu-Mei Li; Yong Luo; Kun-Chao Lei; Wen-Jie Kou; Fang Tian; Miao-Zhuang Tian; Te Sha; Shu-Fang Wang; Wen-Jun Cui (Journal of Hydrology, 2025)

Rotenone-driven DNA hypermethylation of the miR-6991–3p promoter induces death of mouse brain organoids - Zeyu Cui; Xin Liu; Xijin Gao; Zhihua Yu; Weidong Pan; Te Liu (Tissue and Cell, 2025)

Challenges and opportunities in using biowaste for sustainable hydroponic netted melon (Cucumis melo L.) cultivation - Yen-Tzu Fan; Zih-Ee Lin; Pei-Te Chiueh; Yu-Pin Lin; Lien-Chieh Cheng; Yu-Shen Cheng; Shu-I Lin; Chihhao Fan (Agricultural Systems, 2025)

Biotransformation: a novel approach for the production of 6-hydroxyluteolin 7- O -methylglucuronide compound with antioxidant and anti-inflammatory potential - Chien-Yu Wu; Muddasir Khan; Hsiou-Yu Ding; Tzi-Yuan Wang; Yi-Xuan Li; Chun-Wei Liu; Jiumn-Yih Wu; Te-Sheng Chang (Natural Product Research, 2025)

Self-healing conductive polymer maltose polyborosiloxane matrix for motion detection and imperceptible pulse sensing - Ching-Te Kuo; Kuan-Yu Tu; Guan-Ze Song; Lung-Hao Hu (Chemical Engineering Journal, 2025)

Cementing the grain boundary defects in the strain relaxed mixed Sn-Pb perovskite solar cells - Abhishek Kumar; Zeeshan Alam Ansari; Chintam Hanmandlu; Soumallya Banerjee; Yu-Te Chen; Po-Yu Yang; Ahmed Fouad Musa; Yun-Wen You; Chun-Wei Pao; Tzu-Chien Wei; Jing-Jong Shyue; Yu-Jung Lu; et al. (Chemical Engineering Journal, 2025)

The significance of organophosphate flame retardants in patients with esophageal squamous cell carcinoma - Hung-I Lu; Wan-Ting Huang; Wen-Chin Lee; Fu-Jen Cheng; Chia-Te Kung; Chin-Chou Wang; Liang-Jen Wang; Yu-Che Ou; Shau-Hsuan Li (Environmental Geochemistry and Health, 2025)

A simulation-enabled slope digital twin for real-time assessment of rain-induced landslides - Lu-Yu Ju; Te Xiao; Jian He; Wei-Fan Xu; Shi-Hao Xiao; Li-Min Zhang (Engineering Geology, 2025)

Spatiotemporal response of agricultural drought to meteorological drought in the upper Hanjiang River Basin from three-dimensional perspective - Shenghong Liu; Shaokang Yang; Ji Liu; Te Zhang; Qingxia Lin; Wenjuan Chang; Tao Peng; Dan Yu (Agricultural and Forest Meteorology, 2025)

Surveillance and genetic diversity of bovine viral diarrhea virus in dairy herds across Taiwan - Fong-Yuan Lin; Hau-You Tzeng; Ching-Yu Tseng; Ruei-Sheng Tsai; Mami Oba; Tetsuya Mizutani; Yumiko Yamada; Hue-Ying Chiou; Shih-Te Chuang; Wei-Li Hsu (The Veterinary Journal, 2025)

Microplastic contamination in the gastrointestinal tracts of larval fish assemblages from coastal waters in southwestern Taiwan - Ming-Yih Leu; Sun-Hon Lin; Te-Yu Chen; Fung-Chi Ko; Shao-Hung Peng (Regional Studies in Marine Science, 2025)

Barium uptake and isotope fractionation by a marine diatom: Implications for oceanic barium cycle - Yu-Te Hsieh; Po-Kai Yang; Tung-Yuan Ho (Geochimica et Cosmochimica Acta, 2025)

Chitin nanofiber-stabilized pickering emulsion interacting with egg white protein: Structural features, interfacial properties, and stability - Zhouyi Xiong; Te Yu; Jiran Lv; Jihui Wang; Xing Fu (Food Hydrocolloids, 2025)

Reversal of Extreme Drought-Induced Plant Nitrogen and Phosphorus Imbalances in Grassland - Xiao-Sa Liang; Zheng-Wen Wang; Wentao Luo; Lin Song; Wang Ma; Niwu Te; Qiang Yu; Xing-Guo Han; Xiao-Tao Lü (Ecosystems, 2025)

Examining the influence of PM2.5-bound metallic elements and potential sources on stroke emergency department visits: A case-crossover study in Taiwan - Miku Kono; Ting-Yao Su; Yu-Yin Chang; Charles Chung-Kuang Chou; Chung-Te Lee; Pau-Chung Chen; Wei-Te Wu (Environmental Pollution, 2025)

Development of an oral vaccine delivery system for shrimp aquaculture using attenuated Listeria monocytogenes - Jeff Chia-Kai Hsu; Te-Ken Hsu; Shuh-Bing Guan; Po-Wei Chi; Chih-Ying Chiang; Colin William Pouton; Zi-Wey Wong; Po-Yu Huang; Li-Li Chen (Aquaculture, 2025)

Resource recovery from spent crystalline-silicon solar modules by using microwave pyrolysis, acid leaching and chemical etching - Yu-Fong Huang; Ting-Ting Cheng; Pei-Te Chiueh; Shang-Lien Lo (Process Safety and Environmental Protection, 2025)

Methane Index and TEX86 values in cold seep sediments: Implications for paleo-environmental reconstructions - Sze Ling Ho; Yu-Shih Lin; Pei-Ling Wang; Tzu-Ting Chen; Pei-Ting Lee; Hui-Hsin Wang; Tzu-Jung Cheng; Yun-Ju Wang; Chih-Chieh Su; Min-Te Chen (Geochimica et Cosmochimica Acta, 2025)

A zero-waste approach to Sarcodia suiae valorization: Recycling aquaculture wastes and carbon dioxide for biostimulant, biofertilizer, and bioenergy production - Te-Yuan Chen; Yu-Yun Zheng; Yu-Hsin Wang; Chia-Chen Yeh; Chin-Hsin Liao; Tse-Min Lee (Bioresource Technology, 2025)

CD33 Ameliorates Surgery-Induced Spatial Learning and Memory Impairments Through TREM2 - Jie Zou; Yaxuan Wang; Xinyue Zhang; Xue Pan; Te Fang; Dasheng Cai; Lili Guo; Yu Li; Yi He; Xuezhao Cao (Molecular Neurobiology, 2025)

Intrasporangium zincisolvens sp. nov., A Novel Actinobacterium Isolated from Rhizosphere Soil - Lu-Yao Feng; Jiang‑Yuan Zhao; Zhu-Feng Shi; Ming‑Gang Li; Te Pu; Zhu-Li Shi; Xin Liu; Yu Wang; Le‑Le Li; Pei‑Wen Yang (Current Microbiology, 2025)

Grassland bud and shoot demographic responses to single and recurrent droughts vary across an aridity gradient - Niwu Te; Robert J. Griffin‐Nolan; Ingrid J. Slette; Yuan Shi; Lin Song; Jiaqi Chen; Hongqiang Wang; Jianqiang Qian; Qiang Yu; Zhengwen Wang; Xiaotao Lü; Xingguo Han; et al. (Ecology, 2025)
Clonal demographic traits play important roles in regulating community dynamics. Yet, it remains unclear how the responses of these clonal traits to drought might depend on previous drought exposure, and how drought responses vary among grasslands. We conducted a repeated drought experiment across four grasslands along an aridity gradient in northern China. We assessed the effects of single (precipitation reduction in 2021–2022) versus recurrent (precipitation reduction in 2015–2018 and 2021–2022) drought on bud density, shoot density, and the ratio of bud to shoot density. Drought reduced bud density at all grasslands and shoot density at most grasslands. Drought reduced the ratio of bud‐to‐shoot density only in the most arid grasslands. Recurrent drought had larger negative effects than a single drought on bud density and composition of bud and shoot at only one of four grasslands, and on shoot density at two of four grasslands. Our results suggest that previous drought exposure can alter the response of plant clonal demographic traits to subsequent drought in some but not all grasslands, and that responses can vary with mean climate.

Performance of Convolutional Neural Network Models in Meningioma Segmentation in Magnetic Resonance Imaging: A Systematic Review and Meta-Analysis - Ting-Wei Wang; Jia-Sheng Hong; Wei-Kai Lee; Yi-Hui Lin; Huai-Che Yang; Cheng-Chia Lee; Hung-Chieh Chen; Hsiu-Mei Wu; Weir Chiang You; Yu-Te Wu (Neuroinformatics, 2024)
Background Meningioma, the most common primary brain tumor, presents significant challenges in MRI-based diagnosis and treatment planning due to its diverse manifestations. Convolutional Neural Networks (CNNs) have shown promise in improving the accuracy and efficiency of meningioma segmentation from MRI scans. This systematic review and meta-analysis assess the effectiveness of CNN models in segmenting meningioma using MRI. Methods Following the PRISMA guidelines, we searched PubMed, Embase, and Web of Science from their inception to December 20, 2023, to identify studies that used CNN models for meningioma segmentation in MRI. Methodological quality of the included studies was assessed using the CLAIM and QUADAS-2 tools. The primary variable was segmentation accuracy, which was evaluated using the Sørensen–Dice coefficient. Meta-analysis, subgroup analysis, and meta-regression were performed to investigate the effects of MRI sequence, CNN architecture, and training dataset size on model performance. Results Nine studies, comprising 4,828 patients, were included in the analysis. The pooled Dice score across all studies was 89% (95% CI: 87–90%). Internal validation studies yielded a pooled Dice score of 88% (95% CI: 85–91%), while external validation studies reported a pooled Dice score of 89% (95% CI: 88–90%). Models trained on multiple MRI sequences consistently outperformed those trained on single sequences. Meta-regression indicated that training dataset size did not significantly influence segmentation accuracy. Conclusion CNN models are highly effective for meningioma segmentation in MRI, particularly during the use of diverse datasets from multiple MRI sequences. This finding highlights the importance of data quality and imaging sequence selection in the development of CNN models. Standardization of MRI data acquisition and preprocessing may improve the performance of CNN models, thereby facilitating their clinical adoption for the optimal diagnosis and treatment of meningioma.

Enhanced remediation of textile dyes via nonmetal-modified layered graphitic carbon nitride: Influence of various oxygen precursors - Yu-Tong Huang; Dhanapal Vasu; Yung-Chieh Liu; Arjunan Dhivya Parameswari; Moorthi Pichumani; Tetsu Yonezawa; Hongbing Jia; Te-Wei Chiu (Process Safety and Environmental Protection, 2024)

The role of deep learning in aortic aneurysm segmentation and detection from CT scans: A systematic review and meta-analysis - Ting-Wei Wang; Yun-Hsuan Tzeng; Jia-Sheng Hong; Ho-Ren Liu; Hao-Neng Fu; Yung-Tsai Lee; Wei-Hsian Yin; Yu-Te Wu (Next Research, 2024)

Validation of the constitution in Chinese medicine questionnaires with the newly developed blood-vacuity category: a rare Taiwanese case study - Ting-Yu Huang; Shi-Chen Ou; Wei-Te Huang; Yu-Chuan Lin; Hao-Hsiu Hung; Chin-Wei Chang; Kai-Yuan Hsiao; Yi-Wei Kao; Chien-Hua Wu; Wei-Shan Chang; Ben-Chang Shia; Sheng-Teng Huang (Advances in Traditional Medicine, 2024)

Investigating illicit drug hotspots and daily variations using sewer-network wastewater analysis - Hank Hui-Hsiang Lin; Ming-Chi Hsieh; Jennifer Ia Wen Wen Liu; Yu-Hsiang Wang; Shu-Jie Huang; En Lien; Li-Wei Huang; Pei-Te Chiueh; Hsin-Hsin Tung; Angela Yu-Chen Lin (Chemosphere, 2024)

Maintaining KEAP1 levels in retinal pigment epithelial cells preserves their viability during prolonged exposure to artificial blue light - Ching-Hao Li; Tsung-Min Yang; Ida Fitriana; Te-Chao Fang; Liang-Huan Wu; George Hsiao; Yu-Wen Cheng (Journal of Photochemistry and Photobiology B: Biology, 2024)

To be or not to be: The fate of submerged macrophyte biodiversity in the plateau lakes after restoration for the last decade - Qingxiang Han; Junyao Sun; Qingchuan Chou; Te Cao; Wei Li; Yu Cao (Journal of Environmental Management, 2024)

Rapid green analytical methodology for simultaneous monitoring of nitrosamines and semi-volatile organic compounds in water and human urine samples - Shih-Tao Hu; Uday Shashikumar; Swapnil Gurrani; Yu-Tung Tseng; Karthikeyan Prakasham; Cheng-Te Huang; Anbarasu Krishnan; Chao-En Wang; Po-Chin Huang; Vinoth kumar Ponnusamy (Environmental Geochemistry and Health, 2024)

Retraction Note: Impact of corporate sustainable practices, government initiative, technology usage, and organizational culture on automobile industry sustainable performance - Massoud Moslehpour; Ka Yin Chau; Yu-Te Tu; Khanh-Linh Nguyen; Momodou Barry; Kamasani Dhanasekhar Reddy (Environmental Science and Pollution Research, 2024)

Cellulose acetate-coated capacitive sensor for determining carbon-cycle enzymes activity and as a microbial Indicator for soil health - Chung-Ting Cheng; Yu-Lin Wu; Yung-Te Hou; Tzong-Jih Cheng (Science of The Total Environment, 2024)

Metal recovery from copper indium gallium selenide solar cells by using microwave pyrolysis, thermal oxidation and thermal chlorination - Yu-Fong Huang; Yuedong Chen; Pei-Te Chiueh; Shang-Lien Lo (Process Safety and Environmental Protection, 2024)

Wastewater-based epidemiology to monitor 68 NPS/conventional drug use in Taipei metropolitan area in Taiwan during and after COVID-19 pandemic - Te-Tien Ting; Pin-Chuan Chen; Ya-Chi Chang; Pin-Ju Chiang; Hsu-Cheng Li; Shih-Hsun Chen; Pei-Chieh Chen; Hai-Tien Chu; Ping-Yu Chuang; Yi-Hsin Liu; Pai-Shan Chen (Journal of Hazardous Materials, 2024)

Stiphodon chlorestes , a new species of sicydiine goby ( Teleostei: Gobioidei ) from Taiwan and Luzon - Wei‐Cheng Jhuang; Al Casane Dimaquibo; Te‐Yu Liao (Journal of Fish Biology, 2024)
Stiphodon chlorestes sp. nov. is described based on seven specimens collected from Taiwan and Luzon. It is a large‐sized Stiphodon species sharing the second dorsal‐fin rays 9–10 and pectoral‐fin rays 14–16 with similar‐sized congeners. However, it differs from them by the wider interorbital width and almost complete lack of scales on the occipital region in males. In addition, the new species can be further distinguished from all congeners by seven to eight oval bands or a black longitudinal band on the lower body, black and white spots on pectoral fins, and a short red or orange line on posterior upper edge of caudal fin. Molecular analysis based on the 680‐bp mitochondrial cytochrome oxidase subunit I (COI) fragments also supports it as a distinct species belonging to the “ Stiphodon elegans group” and a sister group of the clade consisting of Stiphodon multisquamus and Stiphodon palawanensis .

Assessing the impact of specific PM2.5-Bound metallic elements on asthma emergency department visits: A case-crossover study in Taiwan - Miku Kono; Ting-Yao Su; Yu-Yin Chang; Charles Chung-Kuang Chou; Chung-Te Lee; Pau-Chung Chen; Wei-Te Wu (Environmental Research, 2024)

Deep Learning Models for Aorta Segmentation in Computed Tomography Images: A Systematic Review And Meta-Analysis - Ting-Wei Wang; Yun-Hsuan Tzeng; Jia-Sheng Hong; Ho-Ren Liu; Kuan-Ting Wu; Hao-Neng Fu; Yung-Tsai Lee; Wei-Hsian Yin; Yu-Te Wu (Journal of Medical and Biological Engineering, 2024)
Purpose This systematic review and meta-analysis was conducted to evaluate the usefulness of deep learning (DL) models for aorta segmentation in computed tomography (CT) images. Methods Adhering to 2020 PRISMA guidelines, we systematically searched PubMed, Embase, and Web of Science for studies published up to March 13, 2024, that used DL models for aorta segmentation in adults’ chest CT images. We excluded studies that did not use DL models, involved nonhuman subjects or aortic diseases (aneurysms and dissections), or lacked essential data for meta-analysis. Segmentation performance was evaluated primarily in terms of Dice scores. Subgroup analyses were performed to identify variations related to geographical location and methodology. Results Our review of 16 studies indicated that DL models achieve high segmentation accuracy, with a pooled Dice score of 96%. We further noted geographical variations in model performance but no significant publication bias, according to the Egger test. Conclusion DL models facilitate aorta segmentation in CT images, and they can therefore guide accurate, efficient, and standardized diagnosis and treatment planning for cardiovascular diseases. Future studies should address the current challenges to enhance model generalizability and evaluate clinical benefits and thus expand the application of DL models in clinical practice.

Retraction Note: Role of energy consumption and sustainability-oriented eco-innovation on economic growth: evidence from Middle Eastern economy - Yu-Te Tu; Chia-Yang Lin; Syed Ehsanullah; Nguyen Ho Viet Anh; Khoa Dang Duong; Pham Quang Huy (Environmental Science and Pollution Research, 2024)

Influence of gestational hypertension and maternal air pollutant exposure on birth outcomes - Tai-Ho Hung; Te-Yao Hsu; Jie Hsu; Chia-Yu Ou; Pi-Hua Liu; Liang-Ming Lo; Steven W Shaw; Gwo-Hwa Wan (Environmental Science and Pollution Research, 2024)

Capnesterones A and B, new steroids isolated from the soft coral Capnella imbricata - Ting-Yu Cheng; Chia-Jung Yang; Po-Jen Chen; Yu-Li Chen; Bo-Rong Peng; Te-An Kung; Zhi-Hong Wen; Kuei-Hung Lai; Hsu-Ming Chung (Phytochemistry Letters, 2024)

Columnar aerosol types and compositions over peninsular Southeast Asia based on long-term AERONET data - Sheng-Hsiang Wang; Hsiang-Yu Huang; Che-Hsuan Lin; Shantanu Kumar Pani; Neng-Huei Lin; Chung-Te Lee; Serm Janjai; Brent N. Holben; Somporn Chantara (Air Quality, Atmosphere & Health, 2024)
Aerosol chemical components such as black carbon (BC) and brown carbon (BrC) regulate aerosol optical properties, which in turn drive the atmospheric radiative forcing estimations due to aerosols. In this study, we used the long-term measurements from AERONET (Aerosol Robotic Network) to better understand the aerosol types and composition with respect to their seasonal and spatial variabilities in peninsular Southeast Asia (PSEA, here defined as Vietnam, Cambodia, Thailand, Laos, and Myanmar). Two methods (i.e., aerosol type cluster and aerosol component retrieval) were applied to determine the aerosol type and chemical composition during the biomass-burning (BB) season. AERONET sites in northern PSEA showed a higher AOD (aerosol optical depth) compared to that of southern PSEA. Differences in land use pattern, geographic location, and weather regime caused much of the aerosol variability over PSEA. Lower single-scattering albedo (SSA) and higher fine-mode fraction (FMF) values were observed in February and March, suggesting the predominance of BB type aerosols with finer and stronger absorbing particles during the dry season. However, we also found that the peak BB month (i.e., March) in northern PSEA may not coincide with the lowest SSA once dust particles have mixed with the other aerosols. Furthermore, we investigated two severe BB events in March of 2014 and 2015, revealing a significant BrC fraction during BB event days. On high AOD days, although the BC fraction was high, the BrC fraction remained low due to lack of aerosol aging. This study highlights the dominance of carbonaceous aerosols in the PSEA atmosphere during the BB season, while also revealing that transported dust particles and BrC aerosol aging may introduce uncertainties into the aerosol radiative forcing calculation.

Controls on distributions of aluminium, manganese and cobalt in the South Atlantic Ocean along GEOTRACES transect GA10 - Xue-Gang Chen; Angela Milne; Jessica K. Klar; Martha Gledhill; Maeve C. Lohan; Yu-Te Hsieh; Gideon M. Henderson; E. Malcolm S. Woodward; Eric P. Achterberg (Geochimica et Cosmochimica Acta, 2024)

Extinction coefficient of dry and deliquescent chemical components of PM_(2.) 5 in urban areas and their impacts on visibility deterioration - Chien-Hao Lin; Shao-En Sun; Chung-Te Lee; Ting-Yu Chiang; Shih-Yu Chang; Tzu-Shuan Wu; Hsin-Yu Wei; Ling-Ya Chen; Hao-Wei Liu; Sally C.W. Tai (Atmospheric Pollution Research, 2024)

Lack of effects of eight-week left dorsolateral prefrontal theta burst stimulation on white matter macro/microstructure and connection in autism - Chun-Hung Yeh; Po-Chun Lin; Rung-Yu Tseng; Yi-Ping Chao; Chen-Te Wu; Tai-Li Chou; Rou-Shayn Chen; Susan Shur-Fen Gau; Hsing-Chang Ni; Hsiang-Yuan Lin (Brain Imaging and Behavior, 2024)

Drivers of Environmental Performance in Asian economies: Do natural resources, green innovation and Fintech really matter? - Yu-Te Tu (Resources Policy, 2024)

Two-dimensional heterojunction layered graphene oxide/graphitic carbon nitride photocatalyst for removal of toxic environmental dye methylene blue - Homg-Ming Su; Dhanapal Vasu; Shang-Yu Chan; Yung-Chieh Liu; Jiaxin Jiang; Yu-Feng You; Te-Wei Chiu; Sheng-Chi Chen (Environmental Pollution, 2024)

Isolation and characterization of the novel phage BP14 for lysing Vibrio parahaemolyticus and reducing virulence proteins - Te-Ken Hsu; Hui-Yu Shih; Hui-Ju Huang; Jeff Chia-Kai Hsu; Han-Ching Wang; Yi-Yin Chen; Li-Li Chen (Aquaculture, 2024)

Multifunctional hollow spherical delafossite: Massive electrocatalyst for water splitting and photocatalytic degradation of furaltadone antibiotic wastewater - Yu-Feng You; Dhanapal Vasu; Jiaxin Jiang; Yung-Chieh Liu; Chun-Han Tsang; Te-Wei Chiu; Liangdong Fan (Journal of Water Process Engineering, 2024)

Grassland sensitivity to drought is related to functional composition across E ast A sia and N orth A merica - Lin Song; Robert J. Griffin‐Nolan; Taofeek O. Muraina; Jiaqi Chen; Niwu Te; Yuan Shi; Kenneth D. Whitney; Bingchuan Zhang; Qiang Yu; Melinda D. Smith; Xiaoan Zuo; Zhengwen Wang; et al. (Ecology, 2024)
Plant traits can be helpful for understanding grassland ecosystem responses to climate extremes, such as severe drought. However, intercontinental comparisons of how drought affects plant functional traits and ecosystem functioning are rare. The Extreme Drought in Grasslands experiment (EDGE) was established across the major grassland types in East Asia and North America (six sites on each continent) to measure variability in grassland ecosystem sensitivity to extreme, prolonged drought. At all sites, we quantified community‐weighted mean functional composition and functional diversity of two leaf economic traits, specific leaf area and leaf nitrogen content, in response to drought. We found that experimental drought significantly increased community‐weighted means of specific leaf area and leaf nitrogen content at all North American sites and at the wetter East Asian sites, but drought decreased community‐weighted means of these traits at moderate to dry East Asian sites. Drought significantly decreased functional richness but increased functional evenness and dispersion at most East Asian and North American sites. Ecosystem drought sensitivity (percentage reduction in aboveground net primary productivity) positively correlated with community‐weighted means of specific leaf area and leaf nitrogen content and negatively correlated with functional diversity (i.e., richness) on an intercontinental scale, but results differed within regions. These findings highlight both broad generalities but also unique responses to drought of community‐weighted trait means as well as their functional diversity across grassland ecosystems.

A Low-Cost and High-Precision Underwater Integrated Navigation System - Jiapeng Liu; Te Yu; Chao Wu; Chang Zhou; Dihua Lu; Qingshan Zeng (Journal of Marine Science and Engineering, 2024)
The traditional underwater integrated navigation system is based on an optical fiber gyroscope and Doppler Velocity Log, which is high-precision but also expensive, heavy, bulky and difficult to adapt to the development requirements of AUV swarm, intelligence and miniaturization. This paper proposes a low-cost, light-weight, small-volume and low-computation underwater integrated navigation system based on MEMS IMU/DVL/USBL. First, according to the motion formula of AUV, a five-dimensional state equation of the system was established, whose dimension was far less than that of the traditional. Second, the main source of error was considered. As the velocity observation value of the system, the velocity measured by DVL eliminated the scale error and lever arm error. As the position observation value of the system, the position measured by USBL eliminated the lever arm error. Third, to solve the issue of inconsistent observation frequencies between DVL and USBL, a sequential filter was proposed to update the extended Kalman filter. Finally, through selecting the sensor equipment and conducting two lake experiments with total voyages of 5.02 km and 3.2 km, respectively, the correctness and practicality of the system were confirmed by the results. By comparing the output of the integrated navigation system and the data of RTK GPS, the average position error was 4.12 m, the maximum position error was 8.53 m, the average velocity error was 0.027 m/s and the average yaw error was 1.41°, whose precision is as high as that of an optical fiber gyroscope and Doppler Velocity Log integrated navigation system, but the price is less than half of that. The experimental results show that the proposed underwater integrated navigation system could realize the high-precision and long-term navigation of AUV in the designated area, which had great potential for both military and civilian applications.

Analysis and classification of coffee beans using single coffee bean mass spectrometry with machine learning strategy - Jia-Jen Tsai; Che-Chia Chang; De-Yi Huang; Te-Sheng Lin; Yu-Chie Chen (Food Chemistry, 2023)

Associations of fine particulate matter exposure with sleep disorder indices in adults and mediating effect of body fat - Cheng-Yu Tsai; Huei-Tyng Huang; Ming Liu; Wun-Hao Cheng; Wen-Hua Hsu; Arnab Majumdar; Kang-Yun Lee; Po-Hao Feng; Chien-Hua Tseng; Kuan-Yuan Chen; Yi-Chun Kuan; Jiunn-Horng Kang; et al. (Atmospheric Pollution Research, 2023)

Severity of Liver Cirrhosis Evaluated by Digital Subtraction Angiography Using Quantitative Color-Coding Analysis Before Transarterial Embolization - Lung-Hui Giiang; Chang-Hsien Liu; Chih-Yung Yu; Te-Pao Lin; Hsiang-Cheng Chen; Chun-Jung Juan; Yu-Ching Chou (Journal of Medical and Biological Engineering, 2023)

Description of a new moray eel ( Anguilliformes: Muraenidae ) from the Philippines , with a preliminary assessment of genetic and morphological variations of the Uropterygius concolor species complex - Wen‐Chien Huang; Rodulf Anthony Balisco; Florence Chan Evacitas; Te‐Yu Liao (Journal of Fish Biology, 2023)
Uropterygius concolor Rüppell, the type species of the genus Uropterygius , is a small, uniformly brown moray considered to be widely distributed in the Indo‐Pacific region. However, a recent study indicated that the real U. concolor is currently known only from the type locality in the Red Sea, and species recorded outside the Red Sea may represent a species complex that comprises several species. In this study, we assess the genetic and morphological variations of this species complex based on available data. Analyses of cytochrome c oxidase subunit I sequences revealed at least six distinct genetic lineages recognized under ‘ U. concolor ’. After carefully comparing the morphologies, one of the lineages is described herein as a new species, Uropterygius mactanensis sp. nov., based on 21 specimens collected from Mactan Island, Cebu, Philippines. Another distinct lineage is considered to be a possibly undescribed species based on diagnostic morphological characters. Although the taxonomic status of junior synonyms of U. concolor and some lineages still remain unresolved, this study provides informative morphological characters ( i.e. , tail length, trunk length, vertebrae number, and arrangement of teeth) that can be used in future studies on this species complex.

Edge-based wireless imaging system for continuous monitoring of insect pests in a remote outdoor mango orchard - Dan Jeric Arcega Rustia; Wei-Che Lee; Chen-Yi Lu; Ya-Fang Wu; Pei-Yu Shih; Sheng-Kuan Chen; Jui-Yung Chung; Ta-Te Lin (Computers and Electronics in Agriculture, 2023)

Nexus between natural resource depletion and rent and COP26 commitments: Empirical evidence from Vietnam - Trung Kien Tran; Chia-Yang Lin; Yu-Te Tu; Nam Tien Duong; Thuy Dung Pham Thi; Khamdamov Shoh-Jakhon (Resources Policy, 2023)

Impact of natural resources extraction and energy consumption on the environmental sustainability in ASEAN countries - Tran Thai Ha Nguyen; Yu-Te Tu; Gia Luat Diep; Trung Kien Tran; Nguyen Hoang Tien; FengSheng Chien (Resources Policy, 2023)

Impact of lifetime air pollution exposure patterns on the risk of chronic disease - Cheng-Yu Tsai; Chien-Ling Su; Yuan-Hung Wang; Sheng-Ming Wu; Wen-Te Liu; Wen-Hua Hsu; Arnab Majumdar; Marc Stettler; Kuan-Yuan Chen; Ya-Ting Lee; Chaur-Jong Hu; Kang-Yun Lee; et al. (Environmental Research, 2023)

Marine fishes of Palawan, Philippines: Species diversity, new records, and conservation status - Rodulf Anthony T. Balisco; Victor S. Ticzon; Badi R. Samaniego; Wen-Chien Huang; Benjamin J. Gonzales; Te-Yu Liao (Regional Studies in Marine Science, 2023)

Movement patterns and habitat use of adult giant trevally (Caranx ignobilis) in the South China Sea - Wei-Chuan Chiang; Shian-Jhong Lin; Ker-Yea Soong; Te-Yu Liao; Yu-Yun Chen; Yuan-Shing Ho; Chen-Te Tseng; Michael K. Musyl (Marine Biology, 2023)

CorelKit: An Extensible CorelDraw VBA Program for Geoscience Drawing - Junwu Zhang; Xian Liang; Fangyue Wang; Huaikun Wang; Yu Fan; Te Ba; Xiangxi Meng (Journal of Earth Science, 2023)

Systematics of lionfishes (Scorpaenidae: Pteroini) using molecular and morphological data - Tak-Kei Chou; Min-Yun Liu; Te-Yu Liao (Frontiers in Marine Science, 2023)
Lionfishes (tribe Pteroini) are eye-catching due to their distinct elongated fins and warning coloration. The monophyly of the Pteroini is supported by recent phylogenetic analyses. However, the interrelationships between inter- and intra-genera of the Pteroini are contentious. In this study, 5,335 bps of two mitochondrial and five nuclear genes were sequenced to reconstruct the phylogeny of lionfishes. Our analyses showed Dendrochirus and Pterois were both not monophyletic and divided into Dendrochirus I, II, and III clades ( D . I, II, and III) and Pterois I and II clades ( Pt . I and II), respectively. Pt . I was sister to the Pt . II + D . I clades. D . II was the sister group of the Ebosia + Parapterois clade. The D . III clade was at the base of the Pteroini, followed by the genus Brachypterois . Morphologically, we provided combinations of characters to distinguish all clades. According to the molecular and morphological data, we propose a revised taxonomy of the Pteroini. D . I and Pt . I hold the generic names of Dendrochirus and Pterois , respectively. Neochirus gen. n. is proposed as a new genus for the D. II clade. The genera Pteropterus Swainson, 1839 and Nemapterois Fowler, 1938 are revalidated for Pt. II and D. III, respectively.

Genomic architecture underlying morphological and physiological adaptation to high elevation in a songbird - Chia‐Wei Lu; Shih‐Ting Huang; Shun‐Jen Cheng; Chen‐Tau Lin; Yu‐Cheng Hsu; Cheng‐Te Yao; Feng Dong; Chih‐Ming Hung; Hao‐Chih Kuo (Molecular Ecology, 2023)
Organisms often acquire physiological and morphological modifications to conquer ecological challenges when colonizing new environments which lead to their adaptive evolution. However, deciphering the genomic mechanism of ecological adaptation is difficult because ecological environments are often too complex for straightforward interpretation. Thus, we examined the adaptation of a widespread songbird—the rufous‐capped babbler ( Cyanoderma ruficeps )—to a relatively simple system: distinct environments across elevational gradients on the mountainous island of Taiwan. We focused on the genomic sequences of 43 birds from five populations to show that the Taiwan group split from its sister group in mainland China around 1–2 million years ago (Ma) and colonized the montane habitats of Taiwan at least twice around 0.03–0.22 Ma. The montane and lowland Taiwan populations diverged with gene flow between them, suggesting strong selection associated with different elevations. We found that the montane babblers had smaller beaks than the lowland ones, consistent with Allen's rule, and identified candidate genes— COL9A1 and SOX11 —underlying the beak size changes. We also found that altitudinally divergent mutations were mostly located in noncoding regions and tended to accumulate in chromosomal inversions and autosomes. The altitudinally divergent mutations might regulate genes related to haematopoietic, metabolic, immune, auditory and vision functions, as well as cerebrum morphology and plumage development. The results reveal the genomic bases of morphological and physiological adaptation in this species to the low temperature, hypoxia and high UV light environment at high elevation. These findings improve our understanding of how ecological adaptation drives population divergence from the perspective of genomic architecture.

Behaviour of FRP spiral-confined concrete and contribution of FRP longitudinal bars in FRP-RC columns under axial compression - Jun-Jie Zeng; Yu-Yi Ye; Wei-Te Liu; Yan Zhuge; Yue Liu; Qing-Rui Yue (Engineering Structures, 2023)

Eicosane-based thermo-conductive phase change composite for efficient capture solar energy and using in real-environment as power source - Linhong Li; Maohua Li; Yue Qin; Yapeng Chen; Wen Dai; Zhenbang Zhang; Xiangdong Kong; Ping Gong; Yandong Wang; Rongjie Yang; Bo Wang; Tao Cai; et al. (Chemical Engineering Journal, 2023)

Microwave synthesis of boron- and nitrogen-codoped graphene quantum dots and their detection to pesticides and metal ions - Chien-Te Hsieh; Po-Yu Sung; Yasser Ashraf Gandomi; Kuan Shiong Khoo; Jeng-Kuei Chang (Chemosphere, 2023)

Classifying Temporomandibular Disorder with Artificial Intelligent Architecture Using Magnetic Resonance Imaging - Zih-Kai Kao; Neng-Tai Chiu; Hung-Ta Hondar Wu; Wan-Chen Chang; Ding-Han Wang; Yen-Ying Kung; Pei-Chi Tu; Wen-Liang Lo; Yu-Te Wu (Annals of Biomedical Engineering, 2023)

Ambient relative humidity-dependent obstructive sleep apnea severity in cold season: A case-control study - Kuan-Jen Bai; Wen-Te Liu; Yuan-Chien Lin; Yansu He; Yueh-Lun Lee; Dean Wu; Ta-Yuan Chang; Li-Te Chang; Chun-Yeh Lai; Cheng-Yu Tsai; Kian Fan Chung; Kin-Fai Ho; et al. (Science of The Total Environment, 2023)

Dynamic life cycle assessment for water treatment implications - Huan-Yu Shiu; Mengshan Lee; Zih-Ee Lin; Pei-Te Chiueh (Science of The Total Environment, 2023)

Toxic environmental drug nimesulide detection and degradation using the Bi-functional vanadium and phosphorous doped graphitic carbon nitride nanosheets - Dhanapal Vasu; Arjunan Karthi Keyan; Pichumani Moorthi; Subramanian Sakthinathan; Chung-Lun Yu; Te-Wei Chiu (Journal of Environmental Chemical Engineering, 2023)

Cadmium exposure and risk of breast cancer: A meta-analysis - VA. Florez-Garcia; EC. Guevara-Romero; MM. Hawkins; LE. Bautista; TE. Jenson; J. Yu; AE. Kalkbrenner (Environmental Research, 2023)

Power laws for accurate determination of landslide volume based on high-resolution LiDAR data - Lu-Yu Ju; Li-Min Zhang; Te Xiao (Engineering Geology, 2023)

Hydroxychloroquine repairs burn damage through the Wnt/β-catenin pathway - Sheau-Chung Tang; Chun-Te Lu; Jiunn-Liang Ko; Cheng-Hui Lin; Yu-Ping Hsiao (Chemico-Biological Interactions, 2023)

RETRACTED ARTICLE: Role of energy consumption and sustainability-oriented eco-innovation on economic growth: evidence from Middle Eastern economy - Yu-Te Tu; Chia-Yang Lin; Syed Ehsanullah; Nguyen Ho Viet Anh; Khoa Dang Duong; Pham Quang Huy (Environmental Science and Pollution Research, 2023)

Development of the dried blood spot preparation protocol for comprehensive evaluation of the hematocrit effect - Chih-Ning Cheng; Yu-Fong Peng; Ju-Yu Chen; Guan-Yuan Chen; Te-I Weng; Ching-Hua Kuo (Analytica Chimica Acta, 2023)

The role of economic conditions and sustainable rural development on the sustainability of tourism development: evidence from China - Chenlei Xue; Yu-Te Tu; Mohammed Ananzeh; Ahmad Ibrahim Aljumah; Lam Minh Trung; Thanh Quang Ngo (Environmental Science and Pollution Research, 2022)
At present, tourism is counted among those industries which have gained global attention due to rapid growth. Hence, a constant diversification in terms of destination is needed in tourism development. The recent trends of industry highlight the demand of alternative tourism types, among which nature-related tourism appears to be an emerging concept. In this regard, the present article investigates the impact of economic conditions and sustainable rural development on the sustainability of tourism development in China. The current research has gathered secondary data from the World Bank from 1981 to 2020. The quartile autoregressive distributed lag model has been applied to test the association between the variables. The results revealed that GDP, inflation, FDI, exchange rate, energy use, gross savings, and sustainable rural development have a significant and positive association with the sustainability of tourism development in China. Findings offer managerial implications recommending the local government to focus on the sustainability of rural development and economic conditions that may lead to the implementation of tourism-related development projects. This study also guides the policymakers in establishing policies related to tourism development using different economic conditions and sustainable rural development.

RETRACTED ARTICLE: Impact of corporate sustainable practices, government initiative, technology usage, and organizational culture on automobile industry sustainable performance - Massoud Moslehpour; Ka Yin Chau; Yu-Te Tu; Khanh-Linh Nguyen; Momodou Barry; Kamasani Dhanasekhar Reddy (Environmental Science and Pollution Research, 2022)

Assessing phenovariant species pairs of moray eels: Hybridization, introgression, and morphology - Wen‐Chien Huang; Hong‐Ming Chen; Yung‐Che Tseng; Te‐Yu Liao (Zoologica Scripta, 2022)
Phenovariant is a pair of populations or species with distinct phenotypes but little to no genetic divergence, which may have resulted from strong assortative mating, hybridization, or incomplete lineage sorting that changes in the phenotype have exceeded the genotype. Previous studies had mainly tackled this issue on small, colourful reef fishes, but little effort has been made to the barely seen and solitary taxa like the morays (family Muraenidae). In the present study, three species pairs of sympatric morays from Taiwanese waters revealed as phenovariant in the mitochondrial cytochrome oxidase I ( COI ) were examined from the molecular and morphological perspectives, with three dissimilar scenarios discovered: (1) no hybridization was found between the morphologically most distinct Gymnothorax intesi and Gymnothorax neglectus ; (2) Gymnothorax kidako bidirectionally hybridized with Gymnothorax prionodon instead of its closely related species Gymnothorax pseudokidako ; and (3) frequently bidirectional hybridization and introgression were detected between Gymnothorax pseudothyrsoideus and Gymnothorax reevesii , a species pair that overlapped in all the morphometric and meristic characters. Nevertheless, the principal component analysis indicated that each species pair has evolved significant morphological divergence, further supporting their taxonomic validities. Our results document the natural hybridization of marine eel taxa for the first time and reveal a diverse evolutionary process among the morays.

Carbon capture of biochar produced by microwave co-pyrolysis: adsorption capacity, kinetics, and benefits - Yu-Fong Huang; Pei-Te Chiueh; Shang-Lien Lo (Environmental Science and Pollution Research, 2022)

Currents shaped the genetic structure of Tridentiger barbatus (Günther 1861) along the Chinese coast - Jiehong Wei; Min-Yun Liu; Jen-Chieh Shiao; Fan Li; Jinquan Yang; Yoshiyuki Iizuka; Bin Kang; Ruo-Shan Tseng; Huan-Jie Shao; Te-Yu Liao (Frontiers in Marine Science, 2022)
The modern coast of China is characterized by complicated hydrology, which might be a potential factor shaping genetic structure of marine organisms. Tridentiger barbatus is a widespread benthic goby in coastal China whose range expansion might depend on larval dispersal in its spawning season. We explored the genetic structure of T. barbatus and its interrelationships with coastal currents, planktonic larval duration, and Pleistocene climate fluctuations. Genealogies of Cytb , Rh , and RAG1 reveal two lineages in T. barbatus , namely the southern and northern lineages. The southern lineage is distributed through the South China Sea to the South Yellow Sea but is absent from the North Yellow Sea and Bohai Sea. The HYCOM average flow field indicates an eddy between the North and South Yellow Seas, which might cause larval retention and limit dispersal of the southern lineage into the North Yellow Sea and the Bohai Sea. The northern lineage is distributed through the South Yellow Sea to the Bohai Sea but is absent from the South China Sea and East China Sea. The distribution of the northern lineage fits the eastward deflection of the Yellow Sea Coastal Current at the boundary of the East China Sea and South Yellow Sea, which might limit southward larval dispersal of the northern lineage into the East China Sea. We also uncovered two Cytb haplotype groups within the southern lineage, namely groups A and B, whose distributions might be shaped by the northward Taiwan Strait Current. The coincidence between the genetic structure of T. barbatus and the coastal currents and eddies strongly implies significant roles of larval dispersal and current transportation in shaping the genetic structure of T. barbatus . In addition, significant isolation by distance is found in the southern lineage, which coincides with its short planktonic larval duration (20–30 days). The inference on divergence time suggests that the observed lineages and haplotype groups in T. barbatus originated in the Pleistocene glaciations. Therefore, the coastal currents, planktonic larval duration, and historical glacial isolation are proposed as important factors shaping the genetic structure of T. barbatus .

Nature-based solutions for securing contributions of water, food, and energy in an urban environment - Mei-Hua Yuan; Fang-Chen Lo; Chang-Ping Yu; Hsin-hsin Tung; Yu-Sen Chang; Pei-Te Chiueh; Hsin-Chieh; Huang; Chao-Chin Chang; Chung-Yu Guan; Chun-Wei Wu; Zi-Xuan Xu; et al. (Environmental Science and Pollution Research, 2022)

Air pollution associated with cognitive decline by the mediating effects of sleep cycle disruption and changes in brain structure in adults - Chen-Chen Lo; Wen-Te Liu; Yueh-Hsun Lu; Dean Wu; Chih-Da Wu; Ting-Chieh Chen; Yu-Ting Fang; Yu-Chun Lo; You-Yin Chen; Lo Kang; Cheng-Yu Tsai; Yueh-Lun Lee; et al. (Environmental Science and Pollution Research, 2022)

The impacts of ambient relative humidity and temperature on supine position-related obstructive sleep apnea in adults - Wen-Te Liu; Yuan-Hung Wang; Li-Te Chang; Chih-Da Wu; Dean Wu; Cheng-Yu Tsai; Chen-Chen Lo; Kang Lo; Kian Fan Chung; Ta-Yuan Chang; Kai-Jen Chuang; Yueh-Lun Lee; et al. (Environmental Science and Pollution Research, 2022)

Interleukin-6 transiently promotes proliferation of osteoclast precursors and stimulates the production of inflammatory mediators - Peng-Yuan Chang; Hung-Kang Wu; Yu-Hsu Chen; Yu-Pao Hsu; Ming-Te Cheng; Ching-Hsiao Yu; Shau-Kwaun Chen (Molecular Biology Reports, 2022)

Legacy effects of a multi-year extreme drought on belowground bud banks in rhizomatous vs bunchgrass-dominated grasslands - Jianqiang Qian; Ziyue Guo; Taofeek O. Muraina; Niwu Te; Robert J. Griffin-Nolan; Lin Song; Chong Xu; Qiang Yu; Zhiming Zhang; Wentao Luo (Oecologia, 2022)

Not out of the woods yet: Signatures of the prolonged negative genetic consequences of a population bottleneck in a rapidly re‐expanding wader, the black‐faced spoonbill Platalea minor - Shou‐Hsien Li; Yang Liu; Chia‐Fen Yeh; Yuchen Fu; Carol K. L. Yeung; Chun‐Cheng Lee; Chi‐Cheng Chiu; Tung Hui Kuo; Fang‐Tse Chan; Yu‐Chia Chen; Wen‐Ya Ko; Cheng‐Te Yao (Molecular Ecology, 2022)
The long‐term persistence of a population which has suffered a bottleneck partly depends on how historical demographic dynamics impacted its genetic diversity and the accumulation of deleterious mutations. Here we provide genomic evidence for the genetic effect of a recent population bottleneck in the endangered black‐faced spoonbill ( Platalea minor ) after its rapid population recovery. Our data suggest that the bird's effective population size, N e , had been relatively stable (7500–9000) since 22,000 years ago; however, a recent brief yet severe bottleneck ( N e = 20) which we here estimated to occur around the 1940s wiped out >99% of its historical N e in roughly three generations. Despite a >15‐fold population recovery since 1988, we found that black‐faced spoonbill population has higher levels of inbreeding (7.4 times more runs of homozygosity) than its sister species, the royal spoonbill ( P. regia ), which is not thought to have undergone a marked population contraction. Although the two spoonbills have similar levels of genome‐wide genetic diversity, our results suggest that selection on more genes was relaxed in the black‐faced spoonbill; moreover individual black‐faced spoonbills carry more putatively deleterious mutations (Grantham's score > 50), and may therefore express more deleterious phenotypic effects than royal spoonbills. Here we demonstrate the value of using genomic indices to monitor levels of genetic erosion, inbreeding and mutation load in species with conservation concerns. To mitigate the prolonged negative genetic effect of a population bottleneck, we recommend that all possible measures should be employed to maintain population growth of a threatened species.

Machine learning-enhanced soil classification by integrating borehole and CPTU data with noise filtering - Te Xiao; Hai-Feng Zou; Ke-Sheng Yin; Yu Du; Li-Min Zhang (Bulletin of Engineering Geology and the Environment, 2021)

DNA metabarcoding for dietary analysis of H olland's carp ( Spinibarbus hollandi ) to evaluate the threat to native fishes in T aiwan - Chien‐I Lee; Feng‐Yu Wang; Min‐Yun Liu; Tak‐Kei Chou; Te‐Yu Liao (Journal of Fish Biology, 2021)
DNA metabarcoding analysis for gut contents has been shown to compensate the disadvantage of traditionally morphological identification and offer higher resolution of prey items in an efficient way. Holland's carp ( Spinibarbus hollandi ) is a freshwater fish native to southern and eastern Taiwan. In the past two decades, this species has been introduced as a sport fish into the river basins of northern and western Taiwan. The large body size and active predation make it a potential threat for native fishes, but which native species are preyed by Holland's carp remains unknown. In this study, the diet from the gut contents of Holland's carp from the Zhonggang River, an invaded basin, was examined using DNA metabarcoding from 51 individuals and by morphological examinations on 140 samples. Detritus of plants were found in 83.6% samples (117 individuals). Twenty fish species of seven families were identified by DNA metabarcoding, including species of all water layers. Taiwan torrent carp ( Acrossocheilus paradoxus ) and Rhinogobius spp. are the most common prey items. Based on the results of this study, Holland's carp is considered an opportunistic omnivore because of its diverse diet items, which is an important trait for successful invasive fish species. The population decline of Opsariichthys pachycephalus may not result from the invasion of Holland's carps. Nonetheless, the time lag between successful invasion and the samplings of this study may be a concern because the population size of O. pachycephalus may have declined and become difficult to prey. The Holland's carps consumed the least species in winter; nonetheless, the occurrence frequencies of preys among seasons were not significantly different probably because of limited temperature fluctuation. The smallest Holland's carps consumed the least prey species compared to other size categories, similar to the relationship of prey species number to size of invasive largemouth bass ( Micropterus salmoides ).

Influencing factors and physiochemical changes of embryogenesis through in vitro isolated microspore culture in Brassica species - Yan-Qi Dong; Yu-Hong Gao; Te Zhao; Guang-Qian Ren; Yan-Li Liu; Bin Guan; Rong-Xian Jin; Fei Gao; Yan-Li Zhang; Xiu-Fang Tan; Hong-Cai Zhu; Yu-Hong Zhang; et al. (Biologia, 2021)

Detection of Vestibular Schwannoma on Triple-parametric Magnetic Resonance Images Using Convolutional Neural Networks - Tzu-Hsuan Huang; Wei-Kai Lee; Chih-Chun Wu; Cheng-Chia Lee; Chia-Feng Lu; Huai-Che Yang; Chun-Yi Lin; Wen-Yuh Chung; Po-Shan Wang; Yen-Ling Chen; Hsiu-Mei Wu; Wan-You Guo; et al. (Journal of Medical and Biological Engineering, 2021)
Purpose The first step in typical treatment of vestibular schwannoma (VS) is to localize the tumor region, which is time-consuming and subjective because it relies on repeatedly reviewing different parametric magnetic resonance (MR) images. A reliable, automatic VS detection method can streamline the process. Methods A convolutional neural network architecture, namely YOLO-v2 with a residual network as a backbone, was used to detect VS tumors from MR images. To heighten performance, T1-weighted–contrast-enhanced, T2-weighted, and T1-weighted images were combined into triple-channel images for feature learning. The triple-channel images were cropped into three sizes to serve as input images of YOLO-v2. The VS detection effectiveness levels were evaluated for two backbone residual networks that downsampled the inputs by 16 and 32. Results The results demonstrated the VS detection capability of YOLO-v2 with a residual network as a backbone model. The average precision was 0.7953 for a model with 416 × 416-pixel input images and 16 instances of downsampling, when both the thresholds of confidence score and intersection-over-union were set to 0.5. In addition, under an appropriate threshold of confidence score, a high average precision, namely 0.8171, was attained by using a model with 448 × 448-pixel input images and 16 instances of downsampling. Conclusion We demonstrated successful VS tumor detection by using a YOLO-v2 with a residual network as a backbone model on resized triple-parametric MR images. The results indicated the influence of image size, downsampling strategy, and confidence score threshold on VS tumor detection.

Phenylpropanoids and lignoids from the whole plant of Vaccinium emarginatum and their cytotoxicity against prostate cancer cells - Ping-Chen Tu; Yu-Chia Liang; Ming-Ching Kao; Louis Kuoping Chao; Mei-Hwei Tseng; Te-Ling Lu; Ping-Jyun Sung; Yueh-Hsiung Kuo (Natural Product Research, 2021)

Computed Tomography Super-Resolution Using a Generative Adversarial Network in Bronchoscopy: A Clinical Feasibility Study - Heng-sheng Chao; Tsu-Hui Shiao; Chung-Wei Chou; Fang-Chi Lin; Yu-Te Wu; Der-Ming Liou (Journal of Medical and Biological Engineering, 2021)

Early morphological development of Erromyzon kalotaenia (Teleostei: Gastromyzontidae) - Wei-Cheng Jhuang; Kuo-Hsun Chiu; Te-Yu Liao (Ichthyological Research, 2021)

A review of the genus Strophidon ( Anguilliformes: Muraenidae ), with description of a new species - Wen‐Chien Huang; Anil Mohapatra; Pham The Thu; Hong‐Ming Chen; Te‐Yu Liao (Journal of Fish Biology, 2020)
Strophidon McClelland is a muraenid genus with characteristic appearance of a very elongated body, a large mouth cleft and anteriorly placed eyes. The nomenclature and taxonomic history of species within Strophidon are contentious and its members are easily misidentified. In the present study, species of the genus Strophidon are revised based on morphological and molecular data, and five species are considered valid, including S. dawydoffi Prokofiev, S. dorsalis (Seale), S. sathete (Hamilton), S. ui Tanaka and a new species, S. tetraporus . Strophidon tetraporus sp. nov. is described based on 15 specimens from Indonesia, the Philippines, Taiwan and Vietnam with the unique characteristic of the constant presence of the fourth infraorbital pore among species of Strophidon . The intraspecific variation of vertebral formula within S. dorsalis is discussed based on molecular data. Muraena macrurus Bleeker and Thyrsoidea longissima Kaup are synonyms of S. sathete that can be distinguished from the most similar congener S. ui by a longer tail, smaller eyes and more inner maxillary and inner dentary teeth. A key to identify species of Strophidon is provided. The distribution and maximum size of each species are also re‐evaluated.

Computational comparison of bone cement and poly aryl-ether-ether-ketone spacer in single-segment posterior lumbar interbody fusion: a pilot study - Chih-Wei Chang; Yu-Hsuan Chung; Chia-Jung Chang; Yen-Nien Chen; Chun-Ting Li; Chih-Han Chang; Yao-Te Peng (Physical and Engineering Sciences in Medicine, 2020)

An environmentally friendly strategy for determining organic ultraviolet filters in seawater using liquid-phase microextraction with liquid chromatography–tandem mass spectrometry - Ping-Chang Ku; Ting-Yu Liu; Shu Hui Lee; Te-An Kung; Wei-Hsien Wang (Environmental Science and Pollution Research, 2020)

A full-scale study of external circulation sludge bed (ECSB) system for anaerobic wastewater treatment in a whiskey distillery - Yu-Chung Lin; Chen-Hua Ni; Chin-Yi Wu; Justin Chun-Te Lin (Environmental Science and Pollution Research, 2019)

The Protective Role of Peroxisome Proliferator-Activated Receptor-Gamma in Seizure and Neuronal Excitotoxicity - Te-Yu Hung; Fang-Liang Chu; Dong Chuan Wu; Sheng-Nan Wu; Chin-Wei Huang (Molecular Neurobiology, 2019)

The niches of nuthatches affect their lineage evolution differently across latitude - Yu‐Chi Chen; Masoud Nazarizadeh; Fu‐Min Lei; Xiao‐Jun Yang; Cheng‐Te Yao; Feng Dong; Lu Dong; Fa‐Sheng Zou; Sergei V. Drovetski; Yang Liu; Chun‐Cheng Huang; Chih‐Ming Hung (Molecular Ecology, 2019)
Ecological niche evolution can promote or hinder the differentiation of taxa and determine their distribution. Niche‐mediated evolution may differ among climatic regimes, and thus, species that occur across a wide latitudinal range offer a chance to test these heterogeneous evolutionary processes. In this study, we examine (a) how many lineages have evolved across the continent‐wide range of the Eurasian nuthatch ( Sitta europaea ), (b) whether the lineages’ niches are significantly divergent or conserved and (c) how their niche evolution explains their geographic distribution. Phylogenetic reconstruction and ecological niche models (ENMs) showed that the Eurasian nuthatch contained six parapatric lineages that diverged within 2 Myr and did not share identical climatic niches. However, the niche discrepancy between these distinct lineages was relatively conserved compared with the environmental differences between their ranges and thus was unlikely to drive lineage divergence. The ENMs of southern lineages tended to cross‐predict with their neighbouring lineages whereas those of northern lineages generally matched with their abutting ranges. The coalescence‐based analyses revealed more stable populations for the southern lineages than the northern ones during the last glaciation cycle. In contrast to the overlapping ENMs, the smaller parapatric distribution suggests that the southern lineages might have experienced competitive exclusion to prevent them from becoming sympatric. On the other hand, the northern lineages have expanded their ranges and their current abutting distribution might have resulted from lineages adapting to different climatic conditions in allopatry. This study suggests that niche evolution may affect lineage distribution in different ways across latitude.

Biomechanical response of a submerged, rosette-forming macrophyte to wave action in a eutrophic lake on the Yungui Plateau, China - Guorong Zhu; Guilan Di; Meng Zhang; Te Cao; Leyi Ni; Rongting Fang; Gongliang Yu (Environmental Science and Pollution Research, 2018)

Clinical and microbiological characteristics of peritoneal dialysis-related peritonitis caused by Escherichia coli in southern Taiwan - Wei-Hung Lin; Chin-Chung Tseng; An-Bang Wu; Yu-Tzu Chang; Te-Hui Kuo; Jo-Yen Chao; Ming-Cheng Wang; Jiunn-Jong Wu (European Journal of Clinical Microbiology & Infectious Diseases, 2018)

Impact of Land Use Change on Hydrologic Processes in a Large Plain Irrigation District - Xiao-Bo Luan; Pu-Te Wu; Shi-Kun Sun; Xiao-Lei Li; Yu-Bao Wang; Xue-Rui Gao (Water Resources Management, 2018)

Sodium Metabisulfite: Effects on Ionic Currents and Excitotoxicity - Ming-Chi Lai; Te-Yu Hung; Kao-Min Lin; Pi-Shan Sung; Shyh-Jong Wu; Chih-Sheng Yang; Yi-Jen Wu; Jing-Jane Tsai; Sheng-Nan Wu; Chin-Wei Huang (Neurotoxicity Research, 2018)

Extension of C. elegans lifespan using the ·NO-delivery dinitrosyl iron complexes - Hsiao-Wen Huang; Yen-Hung Lin; Min-Hsuan Lin; Ya-Rong Huang; Chih-Hung Chou; Hsiao-Chin Hong; Mei-Ren Wang; Yu-Ting Tseng; Po-Chun Liao; Min-Chuan Chung; Yu-Jie Ma; Shou-Cheng Wu; et al. (JBIC Journal of Biological Inorganic Chemistry, 2018)

Analysis of land cover and landscape change patterns in Ebinur Lake Wetland National Nature Reserve, China from 1972 to 2013 - Haiyang Yu; Fei Zhang; Hsiang-te Kung; Verner Carl Johnson; Colton Spencer Bane; Juan Wang; Yan Ren; Yue Zhang (Wetlands Ecology and Management, 2017)

Erratum to: Extrapyramidal symptoms after exposure to calcium channel blocker-flunarizine or cinnarizine - Kai-Ming Jhang; Jing-Yang Huang; Oswald Ndi Nfor; Yu-Chun Tung; Wen-Yuan Ku; Chun-Te Lee; Yung-Po Liaw (European Journal of Clinical Pharmacology, 2017)

Extrapyramidal symptoms after exposure to calcium channel blocker-flunarizine or cinnarizine - Kai-Ming Jhang; Jing-Yang Huang; Oswald Ndi Nfor; Yu-Chun Tung; Wen-Yuan Ku; Chun-Te Lee; Yung-Po Liaw (European Journal of Clinical Pharmacology, 2017)

The involvement of supratentorial white matter in multiple system atrophy: a diffusion tensor imaging tractography study - Po-Shan Wang; Chien-Li Yeh; Chia-Feng Lu; Hsiu-Mei Wu; Bing-Wen Soong; Yu-Te Wu (Acta Neurologica Belgica, 2017)

Assessment of different route choice on commuters’ exposure to air pollution in Taipei, Taiwan - Hsien-Chih Li; Pei-Te Chiueh; Shi-Ping Liu; Yu-Yang Huang (Environmental Science and Pollution Research, 2017)

Contribution of urban runoff in Taipei metropolitan area to dissolved inorganic nitrogen export in the Danshui River, Taiwan - Nae-Wen Kuo; Shih-Hao Jien; Nien-Ming Hong; Yao-Te Chen; Tsung-Yu Lee (Environmental Science and Pollution Research, 2017)

Application of Short-Time MSE in Assessing Impact of Acupuncture on Peripheral Blood Flow and Autonomic Activities in Normal and Overweight Subjects - Cheng-Chan Yang; Hsien-Tsai Wu; Wei-Yu Chuang; Te-Chun Liu; I-Ting Tsai; Jian-Jung Chen; Cheuk-Kwan Sun (Journal of Medical and Biological Engineering, 2016)

Regeneration of cerium(IV) in different spent chromium-etching solutions collected from thin-film transistor liquid crystal display manufacturing factories - Kuo-Lin Huang; Te-San Chen; Ren-Wei Tsai; Yu-Syuan Chen (Clean Technologies and Environmental Policy, 2016)

The alterations in regional homogeneity of parieto-cingulate and temporo-cerebellum regions of first-episode medication-naïve depression patients - Chien-Han Lai; Yu-Te Wu (Brain Imaging and Behavior, 2016)

Removal of cyanobacteria from synthetic and real water by dielectric barrier discharge process - Yi Zhang; Stephanie Ting Yu Chew; Shu Harn Te; Tuti Mariana Lim (Environmental Science and Pollution Research, 2015)

Intra-Colonial Functional Differentiation-Related Modulation of the Cellular Membrane in a Pocilloporid Coral Seriatopora caliendrum - Chuan-Ho Tang; Ping-Chang Ku; Ching-Yu Lin; Te-Hao Chen; Kuo-Hsin Lee; Shu-Hui Lee; Wei-Hsien Wang (Marine Biotechnology, 2015)

Genetic relationships and ecological divergence in Salix species and populations in Taiwan - Chun-Lin Huang; Chung-Te Chang; Bing-Hong Huang; Jeng-Der Chung; Jui-Hung Chen; Yu-Chung Chiang; Shih-Ying Hwang (Tree Genetics & Genomes, 2015)

Species delimitation in the C hinese bamboo partridge B ambusicola thoracica ( P hasianidae; A ves) - Chih‐Ming Hung; Hsin‐Yi Hung; Chia‐Fen Yeh; Yi‐Qiang Fu; De Chen; Fumin Lei; Cheng‐Te Yao; Chiou‐Ju Yao; Xiao‐Jun Yang; Yu‐Ting Lai; Shou‐Hsien Li (Zoologica Scripta, 2014)
Although tropical and subtropical Asia harbour a high level of species diversity, their species richness can be underestimated because species which are in fact distinct have not been separately identified. In this study, we delimit B ambusicola thoracica into two full species, the Chinese bamboo partridge ( B. thoracica ) in continental Asia and the Taiwanese bamboo partridge ( B . sonorivox ) on the island of Taiwan, using coalescent‐based multilocus division and diagnosable vocalization patterns. Isolation‐with‐migration analysis indicated that the two bamboo partridges diverged approximately 1.8 million years ago, with gene flow present most probably during the early stages of their divergence. This conclusion supports the hypothesis that diverging lowland lineages spread across the Asian mainland, and continental islands have more opportunities for secondary contact than highland ones when the sea level was low. Our results imply that conservation of biodiversity in tropical and subtropical Asia could be hindered by overlooking numerous ‘hidden’ species and highlight the importance of re‐examining the taxonomic statuses of species in this region traditionally defined as polytypic.

The role of Mss11 in Candida albicans biofilm formation - Pei-Wen Tsai; Yu-Ting Chen; Cheng-Yao Yang; Hsueh-Fen Chen; Te-Sheng Tan; Tzung-Wei Lin; Wen-Ping Hsieh; Chung-Yu Lan (Molecular Genetics and Genomics, 2014)

HSP70 colocalizes with PLK1 at the centrosome and disturbs spindle dynamics in cells arrested in mitosis by arsenic trioxide - Yu-Ju Chen; Kuo-Chu Lai; Hsiao-Hui Kuo; Lu-Ping Chow; Ling-Huei Yih; Te-Chang Lee (Archives of Toxicology, 2014)

Composition of bacterial communities in sand dunes of subtropical coastal forests - Yu-Te Lin; William B. Whitman; David C. Coleman; Tsai-Huei Chen; Chih-Yu Chiu (Biology and Fertility of Soils, 2014)

Medullo-ponto-cerebellar white matter degeneration altered brain network organization and cortical morphology in multiple system atrophy - Chia-Feng Lu; Po-Shan Wang; Yuan-Lin Lao; Hsiu-Mei Wu; Bing-Wen Soong; Yu-Te Wu (Brain Structure and Function, 2014)

Selection and characterization of an acid-resistant mutant of serotype O foot-and-mouth disease virus - Te Liang; Decheng Yang; Mengmeng Liu; Chao Sun; Fang Wang; Jingfei Wang; Haiwei Wang; Shanshan Song; Guohui Zhou; Li Yu (Archives of Virology, 2014)

Genetic variations in TP53 binding sites are predictors of clinical outcomes in prostate cancer patients - Victor C. Lin; Chao-Yuan Huang; Yung-Chin Lee; Chia-Cheng Yu; Ta-Yuan Chang; Te-Ling Lu; Shu-Pin Huang; Bo-Ying Bao (Archives of Toxicology, 2014)

Shape and curvedness analysis of brain morphology using human fetal magnetic resonance images in utero - Hui-Hsin Hu; Hui-Yun Chen; Chih-I Hung; Wan-Yuo Guo; Yu-Te Wu (Brain Structure and Function, 2013)

ER stress and ASK1-JNK activation contribute to oridonin-induced apoptosis and growth inhibition in cultured human hepatoblastoma HuH-6 cells - Duo-te Cai; Hua Jin; Qi-Xing Xiong; Wei-Guang Liu; Zhi-gang Gao; Gui-xiong Gu; Yu-hui Qiu (Molecular and Cellular Biochemistry, 2013)

Differential Legionella spp. survival between intracellular and extracellular forms in thermal spring environments - Po-Min Kao; Min-Che Tung; Bing-Mu Hsu; Shih-Yung Hsu; Jen-Te Huang; Jorn-Hon Liu; Yu-Li Huang (Environmental Science and Pollution Research, 2013)

Using the radium quartet ( 228 Ra, 226 Ra, 224 Ra, and 223 Ra) to estimate water mixing and radium inputs in Loch Etive, Scotland - Yu-Te Hsieh; Walter Geibert; Pieter van-Beek; Henrik Stahl; Dmitry Aleynik; Gideon M. Henderson (Limnology and Oceanography, 2013)
The radium (Ra) quartet ( 228 Ra, 226 Ra, 224 Ra, and 223 Ra) has been investigated in Loch Etive, a Scottish fjord, to provide new constraints on water mixing rates and on the inputs of Ra from sediments. Maximum water transport rates for the inflowing estuarine layer at 5 m depth, determined from the excess 223 Ra ( 223 Ra ex ), indicate that this water travels at no more than 2.4 ± 0.2 cm s −1 net and that it takes 17 ± 2 d for waters to travel from the mouth to the head of the loch if no horizontal mixing is taken into account. Alternatively, neglecting advection, the short‐lived Ra distribution could be explained by horizontal mixing rates of 6.1 × 10 6 cm 2 s −1 ( 223 Ra ex ) or 9.1 × 10 6 cm 2 s −1 ( 224 Ra ex ). Periodic overturning circulation plays an important role in resetting chemical cycles in the isolated deep basin of the inner loch. Sediment in this deep basin provides the major input of 228 Ra to the isolated deep water, and the accumulation of 228 Ra in deep waters allows an assessment of sedimentary fluxes of 228 Ra, a poorly constrained aspect of the 228 Ra input to the global ocean. The calculated sedimentary 228 Ra flux of 2.1 ± 0.2 (× 10 9 ) atoms m −2 yr −1 in the inner deep basin is comparable with previous measurements of sedimentary 228 Ra inputs from shelf sediments, supporting existing global 228 Ra budgets, which are used to assess global rates of groundwater discharge to the ocean.

Hyperinakin, a new anti-inflammatory phloroglucinol derivative from Hypericum nakamurai - Yuan-Bin Cheng; Ahmed Eid Fazary; Yu-Chi Lin; I-Wen Lo; Seow-Chin Ong; Shun-Ying Chen; Ching-Te Chien; Yen-Jung Lin; Wan-Wan Lin; Ya-Ching Shen (Natural Product Research, 2013)

Tail loss compromises immunity in the many-lined skink, Eutropis multifasciata - Chi-Chien Kuo; Chiou-Ju Yao; Te-En Lin; Hsu-Che Liu; Yu-Cheng Hsu; Ming-Kun Hsieh; Wen-San Huang (The Science of Nature, 2013)

Using three-dimensional multigrid-based snake and multiresolution image registration for reconstruction of cranial defect - Yuan-Lin Liao; Chia-Feng Lu; Chieh-Tsai Wu; Jiann-Der Lee; Shih-Tseng Lee; Yung-Nien Sun; Yu-Te Wu (Medical & Biological Engineering & Computing, 2013)

Phylogenetic significance of the kinethmoid‐associated Y‐shaped ligament and long intercostal ligaments in the Cypriniformes (Actinopterygii: Ostariophysi) - TE‐YU LIAO; SVEN O. KULLANDER (Zoologica Scripta, 2013)
Liao, T.Y. & Kullander, S.O. (2012). Phylogenetic significance of the kinethmoid‐associated Y‐shaped ligament and long intercostal ligaments in the Cypriniformes (Actinopterygii: Ostariophysi). — Zoologica Scripta , 42 , 71–87. The phylogenetic significance of the Y‐shaped and long intercostal ligaments in the Cypriniformes is examined using character optimization in 184 species representing 20 non‐ostariophysan teleost species, five ostariophysan orders, seven cypriniform families and 14 cyprinid subfamilies. Character states were optimized on the phylogenetic trees of previous studies. Given the topology of Saitoh et al. (2011) , the Y‐shaped ligament, connecting the kinethmoid to the ethmoid complex, is shown to be a synapomorphy for the Cyprinidae, with reversals observed in the Cyprininae, Danioninae, Gobioninae and Psilorhynchinae. The condition of the Y‐shaped ligament is consistent within most subfamilies with a few exceptions. Despite the exceptions, the Y‐shaped ligament may be considered as a diagnostic character distinguishing cyprinid subfamilies with otherwise similar morphology, that is, the Danioninae and Opsariichthyinae. The long intercostal ligament, connecting five to eight ribs and ascending from the subdistal end of the fifth rib, is present in the Catostomidae and all cyprinid subfamilies, except for the Psilorhynchinae and two developmentally truncated genera, Danionella and Paedocypris . In addition to these two cypriniforme families, the long intercostal ligament is homoplastically present in some catfishes. Given the topology of Saitoh et al. (2011) , presence of the long intercostal ligament is a synapomorphy of Cyprinidae+Catostomidae. Some shorter ligaments are also present in the Cypriniformes and Chilodus gracilis (Characiformes), near the base of the anterior ribs and only occurring anterodorsally to the putative line of the long intercostal ligament even when it is absent.

Influences of extratropical water masses on equatorial Pacific cold tongue variability during the past 160 ka as revealed by faunal evidence of planktic foraminifers - Pai‐Sen Yu; Markus Kienast; Min‐Te Chen; Isabel Cacho; Jos Abel Flores; Mahyar Mohtadi; Alan C. Mix (Journal of Quaternary Science, 2012)
Glacial cooling (∼1–5°C) in the eastern equatorial Pacific (EEP) cold tongue is often attributed to increased equatorial upwelling, stronger advection from the Peru–Chile Current (PCC), and to the more remote subpolar southeastern Pacific water mass. However, evidence is scarce for identifying unambiguously which process plays a more important role in driving the large glacial cooling in the EEP. To address this question, here we adopt a faunal calibration approach using planktic foraminifers with a new compilation of coretop data from the eastern Pacific, and present new downcore variation data of fauna assemblage and estimated sea surface temperatures (SSTs) for the past 160 ka (Marine Isotope Stage (MIS) 6) from ODP Site 1240 in the EEP. With significant improvement achieved by adding more coretop data from the eastern boundary current, our downcore calibration results indicate that most of the glacial cooling episodes over the past 160 ka in the EEP are attributable to increased influence from the subpolar water mass from high latitudes of the southern Pacific. By applying this new calibration of the fauna SST transfer function to a latitudinal transect of eastern Pacific (EP) cores, we find that the subpolar water mass has been a major dynamic contributor to EEP cold tongue cooling since MIS 6. Copyright © 2012 John Wiley & Sons, Ltd.

Diagnosis of Asian Raiamas (Teleostei: Cyprinidae: Chedrina) with comments on chedrin relationships and previously proposed diagnostic characters for Opsaridium and Raiamas - Te Yu Liao; Jairo Arroyave; Melanie L. J. Stiassny (Ichthyological Research, 2012)

An Improved AhR Reporter Gene Assay for Analyzing Dioxins in Soil, Sediment and Fish - How-Ran Chao; Ya-Fan Wang; Yao-Nan Wang; Ding-Yan Lin; Yan-You Gou; Chien-Yu Chen; Kuan-Chung Chen; Wen-Kai Wu; Bao-An Chiang; Yu-Ting Huang; Lien-Te Hsieh; Kuei-Jyum C. Yeh; et al. (Bulletin of Environmental Contamination and Toxicology, 2012)

Ds transposon is biased towards providing splice donor sites for exonization in transgenic tobacco - Kuo-Chan Huang; Hsiu-Chun Yang; Kuan-Te Li; Li-yu Daisy Liu; Yuh-Chyang Charng (Plant Molecular Biology, 2012)

In Vitro and In Vivo Investigation of Drug-Eluting Implants for the Treatment of Periodontal Disease - Fu-Ying Lee; Dave W. Chen; Chih-Chien Hu; Yu-Te Hsieh; Shih-Jung Liu; Err-Cheng Chan (AAPS PharmSciTech, 2011)

Prostaglandin I2 analogues suppress TNF-α expression in human monocytes via mitogen-activated protein kinase pathway - Wei-Li Wang; Chang-Hung Kuo; Yu-Te Chu; Ching-Hua Huang; Ka-Pan Lam; Shau-Ku Huang; Yuh-Jyh Jong; Yu-Ting Kuo; Chih-Hsing Hung (Inflammation Research, 2011)

A hybrid strategy to integrate surface-based and mutual-information-based methods for co-registering brain SPECT and MR images - Yuan-Lin Liao; Yung-Nien Sun; Wan-Yuo Guo; Yuan-Hwa Chou; Jen-Chuen Hsieh; Yu-Te Wu (Medical & Biological Engineering & Computing, 2011)

Three-dimensional reconstruction of cranial defect using active contour model and image registration - Yuan-Lin Liao; Chia-Feng Lu; Yung-Nien Sun; Chieh-Tsai Wu; Jiann-Der Lee; Shih-Tseng Lee; Yu-Te Wu (Medical & Biological Engineering & Computing, 2011)

Effects of PGI2 analogues on Th1- and Th2-related chemokines in monocytes via epigenetic regulation - Chang-Hung Kuo; Ying-Chin Ko; San-Nan Yang; Yu-Te Chu; Wei-Li Wang; Shau-Ku Huang; Huan-Nan Chen; Wan-Ju Wei; Yuh-Jyh Jong; Chih-Hsing Hung (Journal of Molecular Medicine, 2011)

Role of DNA methyltransferase 1 in hormone-resistant prostate cancer - Miao-Fen Chen; Wen-Cheng Chen; Yu-Jia Chang; Ching-Fang Wu; Chun-Te Wu (Journal of Molecular Medicine, 2010)

Bacterial community of very wet and acidic subalpine forest and fire-induced grassland soils - Yu-Te Lin; Ching-Ping Lin; Shu-Miaw Chaw; William B. Whitman; David C. Coleman; Chih-Yu Chiu (Plant and Soil, 2010)

Probiotic Lactobacillus casei Expressing Human Lactoferrin Elevates Antibacterial Activity in the Gastrointestinal Tract - Hsiao-Ling Chen; Yi-Wen Lai; Chua-Shun Chen; Te-Wei Chu; Willie Lin; Chih-Ching Yen; Ming-Fong Lin; Ming-Yu Tu; Chuan-Mu Chen (BioMetals, 2010)

Phylogenetic analysis of the genus Rasbora (Teleostei: Cyprinidae) - Te Yu Liao; Sven O. Kullander; Fang Fang (Zoologica Scripta, 2010)

Isolation and characterization of 23 microsatellite loci in the black-faced spoonbill (Platalea minor) and amplification in other Ciconiiformes waterbirds - Carol K. L. Yeung; Yu-Cheng Hsu; Cheng-Te Yao; Shou-Hsien Li (Conservation Genetics, 2009)

Single-Trial Analysis of Cortical Oscillatory Activities During Voluntary Movements Using Empirical Mode Decomposition (EMD)-Based Spatiotemporal Approach - Po-Lei Lee; Li-Zen Shang; Yu-Te Wu; Chih-Hung Shu; Jen-Chuen Hsieh; Yung-Yang Lin; Chi-Hsun Wu; Yu-Lu Liu; Chia-Yen Yang; Chia-Wei Sun; Kuo-Kai Shyu (Annals of Biomedical Engineering, 2009)

Sensory Acquisition in the Cerebellum: An fMRI Study of Cerebrocerebellar Interaction During Visual Duration Discrimination - Lynn Y. L. Shih; Li-Fen Chen; Wen-Jui Kuo; Tzu-Chen Yeh; Yu-Te Wu; Ovid J. L. Tzeng; Jen-Chuen Hsieh (The Cerebellum, 2009)

Molecular phylogenetic interrelationships of the south Asian cyprinid genera Danio, Devario and Microrasbora (Teleostei, Cyprinidae, Danioninae) - Fang Fang; Michael Norén; Te Yu Liao; Mari Källersjö; Sven O. Kullander (Zoologica Scripta, 2009)
Molecular analysis of mitochondrial cytochrome b sequences from 159 species of the family Cyprinidae supports the subfamily Danioninae, of which Rasborinae is shown to be a junior synonym. Analysis of combined cytochrome b and a fragment of the nuclear rhodopsin gene from 68 species, including 43 species representing the subfamily Danioninae, supports phylogenetic distinctness of Danio and Devario. In the combined molecular analysis Microrasbora rubescens, Chela, Laubuca, Devario, and Inlecypris form a clade with M. gatesi , M. nana and M. kubotai being in sister group position to the rest. The sister group of this Devario clade is Danio . Inlecypris is synonymized with Devario. Microdevario, new genus, is proposed for M. gatesi , M. nana and M. kubotai , supported by morphological characters. In the cytochrome b analysis, M. rubescens falls outside Devario , and there is no morphological support for including M. rubescens in Devario . In the cytochrome b analysis Esomus + Danionella is the sister group of Danio and Devario clades, whereas in individual rhodopsin and combined analyses Esomus is the sister group of Danio , and of Danio and the Devario clade, respectively. Sundadanio presents at least one strong morphological synapomorphy with Danio , but is positioned in molecular trees either as a member of the Cyprininae or as sister group of the remaining Danioninae. In the morphological analysis, small‐sized species grouped together based on shared reductions that are not necessarily synapomorphies. In the molecular analysis, small‐sized species such as Danionella and Sundadanio possess long branches and their position varies, but they did not group together. This suggests morphological homoplasy, but phylogenetic positions are not well supported in the molecular analyses

Effect of calmidazolium on [Ca2+]i and viability in human hepatoma cells - Wei-Chuan Liao; Chorng-Chih Huang; He-Hsiung Cheng; Jue-Long Wang; Ko-Long Lin; Jin-Shiung Cheng; Kuo-Liang Chai; Pei-Te Hsu; Jeng-Yu Tsai; Yi-Chien Fang; Yih-Chau Lu; Hong-Tai Chang; et al. (Archives of Toxicology, 2009)

A study of NO trafficking from dinitrosyl–iron complexes to the recombinant E. coli transcriptional factor SoxR - Feng-Chun Lo; Chang-Li Chen; Chien-Ming Lee; Ming-Che Tsai; Tsai-Te Lu; Wen-Feng Liaw; Steve S.-F. Yu (JBIC Journal of Biological Inorganic Chemistry, 2008)

Blind Source Separation of Concurrent Disease-Related Patterns from EEG in Creutzfeldt–Jakob Disease for Assisting Early Diagnosis - Chih-I Hung; Po-Shan Wang; Bing-Wen Soong; Shin Teng; Jen-Chuen Hsieh; Yu-Te Wu (Annals of Biomedical Engineering, 2007)

The Brain Computer Interface Using Flash Visual Evoked Potential and Independent Component Analysis - Po-Lei Lee; Jen-Chuen Hsieh; Chi-Hsun Wu; Kuo-Kai Shyu; Shyan-Shiou Chen; Tzu-Chen Yeh; Yu-Te Wu (Annals of Biomedical Engineering, 2006)

Assessing Impacts of Typhoons and the Chi-Chi Earthquake on Chenyulan Watershed Landscape Pattern in Central Taiwan Using Landscape Metrics - Yu-pin Lin; Tsun-kuo Chang; Chen-fa Wu; Te-chih Chiang; Shin-hwei Lin (Environmental Management, 2006)

Toluene exposure during the brain growth spurt reduces behavioral responses to noncompetitive N-methyl-d-aspartate receptor antagonists in adult rats - Te-Hsiung Chien; Ming-Huan Chan; Yu-Chi Tang; Hwei-Hsien Chen (Psychopharmacology, 2005)

A Novel Oscillating Bioreactor BelloCell: Implications for Insect Cell Culture and Recombinant Protein Production - Jen-Te Lu; Yao-Chi Chung; Zun-Ren Chan; Yu-Chen Hu (Biotechnology Letters, 2005)

Recognition of Motor Imagery Electroencephalography Using Independent Component Analysis and Machine Classifiers - Chih-I Hung; Po-Lei Lee; Yu-Te Wu; Li-Fen Chen; Tzu-Chen Yeh; Jen-Chuen Hsieh (Annals of Biomedical Engineering, 2005)

Involvement of NO/cGMP pathway in toluene-induced locomotor hyperactivity in female rats - Ming-Huan Chan; Te-Hsiung Chien; Pei-Yu Lee; Hwei-Hsien Chen (Psychopharmacology, 2004)

Comparison of Orthogonal Search and Canonical Variate Analysis for the Identification of Neurobiological Systems - Yu-Te Wu; Mingui Sun; Don Krieger; Robert J. Sclabassi (Annals of Biomedical Engineering, 1999)

Effects of vitamin A pretreatment on nickel-induced lipid peroxidation and concentration of essential metals in liver, kidney and lung of mice - Chang-Yu Chen; Yeou-Lih Huang; Te-Hsien Lin (Archives of Toxicology, 1998)

lipid peroxidation in liver of mice administrated with nickel chloride - Chang-Yu Chen; Yeou-Lih Huang; Te-Hsien Lin (Biological Trace Element Research, 1998)